Monitoring for uninterruptible power supply (UPS) system - Afiq Rahimi, Rosmani (2022)
In industrial process today, reliability of equipment is very important. Power supply must be able to cater the need of industrial process. In case of power failure, backup power supply system must be able to support the main process plant. This is to ensure smooth operation and product quality. In order to do this, uninterruptible power supply (UPS) system can be used to ensure the reliability, stability and consistency of the entire system. This UPS system must be monitored in order to enable them to react accordingly in response to a fault or power failure. In this project, monitoring system for UPS was designed by using battery management system (BMS) to provide a safe and constant 24V DC supply in the case of power disruption. The main power supply, 24V AC was converted to 220V DC as output voltage and a battery will be used as part of the backup system. This system will be able to control the source of power which offers power from LIVE line or power from BATTERY line. The main output voltage was 24V DC and the battery level will be monitored using BMS software.